A COMPARATIVE EVALUATION OF CT SCAN FINDINGS AND POST MORTEM EXAMINATION FINDINGS IN HEAD INJURIES (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
The study pertains to comparative evaluation of CT scan finding and post mortem examination findings in fifty  cases of head injury victims. It was observed that although CT scan is a useful tool for the diagnosis of various  kinds of lesions of head injury, autopsy was found to be more effective in detecting them.
Keywords: Head injury; CT scan findings; Autopsy